ANALISIS ATRIBUT PRODUK TERHADAP PERILAKU PEMBELIAN KONSUMEN SEPATU MEREK NIKE - Maria Margaretha Sumaryati; Gregorius Gregie (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2016)
Exercise is an activity that is much preferred by people who realize the importance of health for the human body. Routinely man sports for the sake of a healthy body crave. Many of them, in addition to doing regular exercise, also does one of the sporting activities with his group as a community or club, e.g. basketball club, badminton club and other clubs. Regular exercise should be carried out in order to face the competition with another group of the same type of field of sport. To sustain such sport activities, sports shoes are required.Consumers must be clever to choose a brand of shoes that meet with some requirements of their need. The purpose of this study is to determine whether there is an influence of the elements of product attributes on consumer purchase behavior of Nike sports shoes. The study was conducted by taking a sample of 100 users of Nike basketball shoes. Data were processed using SPSS program to perform the analysis of overall means score and multiple regression. The results show that the quality of products, product features, product design, product pricing, and product brands significantly influence the intensity of consumer purchases of Nike basketball shoes.